Standardised Warfarin Reversal Expedites Time to Theatre for Fractured Neck of Femur Surgery and Improves Mortality Rates: A Matched Cohort Study - Thomas S. Moores; Benjamin D. Chatterton; Matthew J. Walker; Phillip J. Roberts (Advances in Orthopedics)
Background. This study aims to evaluate outcomes for warfarinised hip fracture patients and compare them with a matched nonwarfarinised group, before and after the introduction of national hip fracture guidelines in the United Kingdom. Methods. A retrospective cohort study of 1743 hip fracture patients was undertaken. All patients admitted taking warfarin were identified. These patients were then matched to nonwarfarinised patients using nearest neighbour propensity score matching, accounting for age, sex, hip fracture type, and Nottingham Hip Fracture Score. A pre-guideline group (no standardised warfarin reversal regimen) and a post-guideline group (standardised regimen) were identified. Outcomes assessed included time to INR less than 1.7, time to theatre, length of stay, and 30-day and 1-year mortality. Results. Forty-six warfarinised hip fracture patients were admitted in the pre-guideline group (mean age 80.5, F:M 3:1) and 48 in the post-guideline group (mean age 81.2 years, F:M 3:1). Post-guideline patients were reversed to a safe operative INR level within 18 hours of admission, decreasing the time to first dose vitamin K (p<0.001). 70% of warfarinised patients were operated upon within 36 hours, compared to 19.6% with no regimen (p<0.05). After anticoagulation reversal protocol, thirty-day mortality decreased from 15.2% to 8.3% and 1-year mortality from 43.5% to 33% for warfarinised patients, which is comparable to nonwarfarinised matched patients. There was no significant change in the length of stay pre- and post-guideline for both groups of patients. Conclusions. Proactive anticoagulant management and expedient surgery reduces morbidity and mortality when managing this surgically challenging subset of hip fracture patients.